Ulama Sebagai Agen Perubahan Mengeksplorasi Peran dan Strategi Psikologis dalam Kampanye Kesehatan di Aceh - Bustami, Bustami; Lahmuddin Lubis (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research focuses on the role and psychological strategies that ulama can play as agents of change in health campaigns in Aceh. Ulama in Aceh have a significant influence in a religious society and respect religious figures. Using a qualitative approach, this research interviewed ulama, health workers and the public to understand their views on the role of ulama in health promotion as well as psychological factors that can influence the success of health campaigns. The research results show that ulama can act as effective health messengers, behavior change agents, and opinion leaders in their communities. Psychological strategies such as persuasion, role modeling, and culture-based approaches can increase public acceptance and participation in health campaigns. However, this research also identified challenges and obstacles faced by ulama, such as lack of knowledge about health, perceptions about the limits of the ulama's role, and cultural barriers. Thus, the findings of this study provide new insight into the importance of ulama involvement in health promotion efforts in Aceh and provide practical recommendations for improving collaboration between ulama and health workers. The implications of these findings can also be applied in other contexts involving religious leaders in health campaigns in religious communities.